KAJIAN EKRANISASI: DARI NOVEL PINTU TERLARANG KE FILM PINTU TERLARANG - Ernest, Yuven Kristianus; Nurgiyantoro, Burhan (Diksi, 2018)
(Title: An Ecranisation Study: From "Pintu Terlarang" Novel into Film). This research is aimed to: (1) describe the changing of the plot in Pintu Terlarang novel into film and (2) describe the changing of characterizations in Pintu Terlarang novel into film through ecranisation. The subject studied was Pintu Terlarang novel by Sekar Ayu Asmara and Pintu Terlarang film (2009) by Joko Anwar. The researcher used recording and note techniques to collect the data and examined in inductive comparative. The result shows that after the ecranisation use of plots and characterizations in the Pintu Terlarang film. The novel used three story lines merged into a movie storyline. The single plot was presented chronologically to describe Gambir's imaginary life which was presented quickly and densely. The film was more highlighted the conflict experienced by Gambir. The film was more dominated by the second sub-story in the novel. The modifications that occured in the film were in the form of reduction of character and duration of appearance, the alteration of position in the story and in physical characteristics, and the addition of the new characters. The changing of the characters was attached to the modification of the use and the function of the characters in the film.Keywords: adaptation, reception, alih wahana, screening, ecranisation, novel, film